EFFECTS OF DRYING PROCESS ON BIOCHEMICAL AND MICROBIOLOGICAL QUALITY OF HORSE MACKEREL FISH (MEGALASPIS CORDYLA) - NEERAJ PATHAK,; S.M. ZOFAIR,; V.B. MULYE,; K.G.BARAIYA, (International Journal of Pharma and Bio Sciences, 2014)
Investigations were carried out on quality changes in salted and dried horse mackerel (Megalaspis cordyla). Sun drying (T1) and mechanical drying (T2) process for fish cured with salt were selected for estimating their efficiency and effect during six months storage period. Sun dried fish showed mean value of moisture, protein, ash and fat as 27.83 %, 54.13 %, 12.95 %, 5.99 %, respectively, while mechanically dried fish exhibited 30.41 %, 52.93 %, 13.14 %, 5.80 % respectively. Other bio-chemical characteristics TMA-N, TVB-N, FFA and PV were 7.72 mg%, 24.45 mg%,6.44 %,8.26 m.equ./kg for T1 and 8.24 mg% , 22.19 mg % ,7.00 %, 78.58. m.equ./kg % for T2 respectively. TPC count were 1.77×105 and 1.91×105 log cfu/g, in T1 and T2 respectively. Sensory score of T2 was higher than T1 and it was statistically significant. The use of mechanical drier for drying of horse mackerel has the added advantage of superior quality and longer shelf life than Sun dried fishes.